Prosaposin is a regulator of progranulin levels and oligomerization - Alexandra M. Nicholson (Nature Portfolio, 2016)
Increasing progranulin (PGRN) levels is a promising approach for treating frontotemporal dementia and other neurodegenerative diseases. Here Nicholson et al.show that the prosaposin (PSAP) locus is associated with plasma PGRN levels and demonstrate that PSAP can alter PGRN levels and its oligomerization.